Design and Development of a Lasem Hand-Drawn Batik Simulation Game - Kevin Wijaya; Erdhi Widyarto Nugroho; T. Brenda Chandrawati (Journal of Business and Technology, 2026)
Lasem, known as "Little China," has a rich cultural heritage, including Batik Lasem, which features distinctive motifs and a complex production process. However, interest among younger generations in the art of batik-making is declining. This study aims to develop a Batik Lasem simulation game as an interactive learning medium for beginners. The game was developed using the Waterfall method with Unity as the primary platform. Testing was conducted using the Unified Theory of Acceptance and Use of Technology (UTAUT) model to analyze user acceptance. This research follows a quantitative approach, collecting data through an online questionnaire with 70 respondents and literature studies. The developed game features two gameplay modes, three difficulty levels, and a simple interface with comfortable audio support. The interactive gameplay allows players to understand each stage of the batik-making process through an intuitive mechanism. The analysis results indicate that usefulness and ease of use play a significant role in increasing user interest in Batik Lasem.